An e-handbook for designing and implementing a benchmarking project. (23rd April 2007) - Margherita, Alessandro; Klein, Mark
Growing competition forces companies to optimise their business processes while enhancing the value of products and services delivered to customers. The comparison with recognised standards or outstanding practices, also belonging to different industries, represents an important checkpoint in this proposal. This paper defines, based on existing approaches, a roadmap to successfully perform a benchmarking initiative. The MIT Process Handbook, an online repository of business knowledge coupled with an innovative process redesign methodology, is thus applied to suggest, through the use of illustrative examples, how purposefully created data, alternatives and tools can be used to implement each phase of the roadmap.